Supercritical Carbon Dioxide Solubility in Hydrophobic Ionic Liquid Mixtures: Experimental Determination and Thermodynamic Modeling - Romero-Figueroa, J; Quijada-Maldonado, E; Villarroel-Utreras, E (Elsevier B.V., 2020)
The solubility of supercritical carbon dioxide (scCO2) in the pure ionic liquids (ILs): 1-hexyl-3-methylimidazolium tris(pentafluoroethyl)trifluorophosphate, [hmim][eFAP], and trihexyltetradecylphosphonium bis(trifluoromethylsulfonyl)imide [P6,6,6,14][Tf2N], and mixtures formed by mixing these ILs with trihexyltetradecylphosphonium tetraphenylborate ([P6,6,6,14][BPh4]), was experimentally measured by means of an equilibrium cell that was designed and assembled to allow obtaining the solubility using small amounts of ILs. This equilibrium cell was first tested using previously published experimental data where long times were necessary to reach equilibrium. However, good agreement with literature data was found. Thus, for pure [hmim][eFAP], the experimental data showed high solubility, which means molalities between 5.96 and 9.12, approximately (mole fractions between 0.78 and 0.85). However, mixing these ILs with 1% w/w [P6,6,6,14][BPh4], decreased or increased CO2 solubility depending on interactions between the ILs. The obtained experimental data was modeled using the vapor-liquid equilibrium relations by means of the Peng-Robinson equation of state and a two-parameter Van der Waals mixing rule, showing excellent agreement. Finally, the information obtained in this work could enable the study of the liquid-liquid phase microextraction with ionic liquids where the dissolution of CO2 in ILs could create an enhanced phase for the microextraction. © 2020 Elsevier B.V.